EDUKASI PENTINGNYA LITERASI KEUANGAN BAGI GENERASI MUDA DI YAYASAN MUTIARA IBU NUSANTARA (YASMIN) - Fitriyah; Silviyani, Yuli Anita; Risthi, Alyssa (Publika Citra Media, 2025)
Research and Community Service (PKM) is one of the manifestations of the Tri Dharma of Higher Education. The purpose of the PKM activity is to foster lecturers in improving their abilities, skills, and independence as well as the existence of Pamulang University as an agent of change in order to provide significant benefits to the community. This time the Unpam Accounting Study Program held PKM to the Mutiara Ibu Nusantara Foundation (Yasmin) in Sawangan Depok. The purpose of the PKM activity at the Mutiara Ibu Nusantara Foundation (Yasmin) is to provide financial literacy training to improve financial knowledge and skills in managing personal finances are very important in everyday life as provisions for their future. The implementation of PKM in the form of presentations of materials, discussions and training at the end of the session to find out how far the material can be absorbed, a question and answer session was held with the students and door prizes were given.